7 × (–3) × (–2)^2 = ? A. –48 B. –84 C. 84 D. 48

Question

Asked 26 days ago|9/11/2024 12:38:26 AM

Updated 26 days ago|9/11/2024 1:07:35 AM

4 Answers/Comments

f
freestar.config.enabled_slots.push({ placementName: 'weegy_incontent_1', slotId: 'weegy_incontent_1' });

Score 1

Score 1

= 2x*3x - 3*3x + 2x*3 - 3*3

= 6x^2 - 9x + 6x - 9

= 6x^2 - 3x - 9

|Score .8061|ydlover08|Points 10|

x - x = 4/3 + 2;

0 = 4/3 + 6/3;

0 = 10/3(FALSE)

NO SOLUTIONS EXIST

|Score 1|rdsa77|Points 8410|

Score 1

1 + 8x = -16 - 9x

8x + 9x = -16 - 1

17x = - 17

x = - 17/17

x = - 1

Score 1

|Score .8222|twistedechoes|Points 46|

Question

Asked 26 days ago|9/11/2024 12:38:26 AM

Updated 26 days ago|9/11/2024 1:07:35 AM

4 Answers/Comments

Rating

3

2 x (-1) x (3)^3

= - 2 x 27

= - 54

= - 2 x 27

= - 54

Added 26 days ago|9/11/2024 1:05:43 AM

This answer has been confirmed as correct and helpful.

3

2x + 3x + 23 -13

= 5x + 10

= 5x + 10

Added 26 days ago|9/11/2024 1:06:02 AM

This answer has been confirmed as correct and helpful.

3

(x+1)(x-2)

= x^2 - 2x + x - 2

= x^2 - x - 2

= x^2 - 2x + x - 2

= x^2 - x - 2

Added 26 days ago|9/11/2024 1:06:41 AM

This answer has been confirmed as correct and helpful.

3

2 + 3x = -4x + 34 - 1

7x = 33 - 2

x = 31/7

7x = 33 - 2

x = 31/7

Added 26 days ago|9/11/2024 1:07:35 AM

This answer has been confirmed as correct and helpful.

39,505,749

questions answered

There are no comments.